The Language of Creativity: Validating Linguistic Analysis to Assess Creative Scientists and Artists - Ahmed, Sana Tariq; Feist, Gregory J. (Frontiers in Psychology, 2021)
The purpose of this study was twofold: first, to be among the first attempts to validate linguistic analysis as a method of creativity assessment and second, to differentiate between individuals in varying scientific and artistic creativity levels using personality language patterns. Creativity is most commonly assessed through methods such as questionnaires and specific tasks, the validity of which can be weakened by scorer or experimenter error, subjective and response biases, and self-knowledge constraints. Linguistic analysis may provide researchers with an automatic, objective method of assessing creativity, free from human error and bias. The current study used 419 creativity text samples from a wide range of creative individuals mostly in science (and some in the arts and humanities) to investigate whether linguistic analysis can, in fact, distinguish between creativity levels and creativity domains using creativity dictionaries and personality dimension language patterns, from the Linguistic Inquiry and Word Count (LIWC) text analysis program. Creative individuals tended to use more words on the creativity keyword dictionaries as well as more Introversion and Openness to Experience Language Pattern words than less creative individuals. Regarding creativity domains, eminent scientists used fewer Introversion and Openness to Experience Language Pattern words than eminent artists. Text analysis through LIWC was able to successfully distinguish between the three creativity levels, in some cases, and the two creativity domains. These findings lend support to the use of linguistic analysis as a partially valid assessment of scientific and artistic creative achievement.